Locus Coeruleus Optogenetic Light Activation Induces Long-Term Potentiation of Perforant Path Population Spike Amplitude in Rat Dentate Gyrus - Quinlan, Meghan A. L.; Strong, Vanessa M.; Skinner, Darlene M.; Martin, Gerard M.; Harley, Carolyn W.; Walling, Susan G. (Frontiers in Systems Neuroscience, 2019)
Norepinephrine (NE) in dentate gyrus produces NE-dependent long-term potentiation of the perforant path-evoked potential population spike (NE-LTP) both in vitro and in vivo. Chemical activators infused near locus coeruleus (LC), the source of dentate gyrus NE, produce a NE-LTP that is associative, i.e., requires concurrent pairing with perforant path input. Here we ask if LC optogenetic stimulation that allows us to activate only LC neurons can induce NE-LTP in dentate gyrus. We use an adeno-associated viral vector containing a depolarizing channel (AAV8-Ef1a-DIO-eChR2(h134r)-EYFP-WPRE) infused stereotaxically into the LC of TH:Cre rats to produce light-sensitive LC neurons. A co-localization of ~ 68% in LC neurons was observed for these channels. Under urethane anesthesia, we demonstrated that 5 and10 sec 10 Hz trains of 30 msec light pulses in LC reliably activated neurons near an LC optoprobe. Ten min of the same train paired with 0.1 Hz perforant path electrical stimulation produced a delayed NE-LTP of population spike amplitude, but not EPSP slope. A leftward shift in the population spike input/output curve at the end of the experiment was also consistent with long-term population spike potentiation. LC neuron activity during the 10 min light train was unexpectedly transient. Increased LC neuronal firing was seen only for the first 2 min of the light train. NE-LTP was more delayed and less robust than reported with LC chemo-activation. Previous estimates of LC axonal conduction times suggest acute release of NE occurs 40-70 msec after an LC neuron action potential. We used single LC light pulses to examine acute effects of NE release and found potentiated population spike amplitude when a light pulse in LC occurred 40-50 msec, but not 20-30 msec, prior to a perforant path pulse, consistent with conduction estimates. These effects of LC optogenetic activation reinforce evidence for a continuum of NE potentiation effects in dentate gyrus. The single pulse effects mirror an earlier report using LC electrical stimulation. These acute effects support an attentional role of LC activation. The long-term potentiation of perforant path responses induced by optogenetic LC activation is consistent with the role of LC in long-term learning and memory.